The Impact of Climatic Factors on Rice Production in Indonesia - Aura Dhamira; Irham Irham (Agro Ekonomi, 2020)
Rice production is greatly affected by climatic factors which keep changing along with time. Therefore, the effects of climate change on rice production in Indonesia need to be studied. The objectives of this study are to determine: (1) the difference of interregional climate in each region and (2) the impact of climatic factors on rice production in Indonesia. Just and Pope Production function was used as the analytical frameworks, and Cobb-Douglas function form was used to analyze the data. The analysis was conducted with regards to rice production in ten provinces in Indonesia from 1985 to 2017. The result shows that there were some differences in climatic condition in each region in Indonesia. The regression analysis shows that maximum temperature and minimum temperature have positive impacts on rice production, on the other hand, El Nino and La Nina affect the production negatively. The results of this study can be considered by the policy makers in making decisions related to adaptation and mitigation on climate change encounter.